Implementasi Otomatisasi Pengujian Fungsional Website Mandala Chain dengan Katalon Studio - Belinda Dwi Sukma Putri; Muchlis Muchlis (Lembaga Pengembangan Kinerja Dosen, 2025)
Mandala Chain is the first layer-1 blockchain developed in Indonesia, focusing on interoperability, data security, and ease of adoption. As a blockchain-based platform, Mandala Chain includes key features such as dashboard, connect wallet, project, develop, and mandala academy, which must be verified for proper functionality. This study aims to test these features automatically using Katalon Studio as an automation testing tool. The research adopts the Software Testing Life Cycle (STLC) approach, consisting of Requirement Analysis, Test Planning, Test Case Development, Test Environment Setup, Test Execution, and Test Cycle Closure. This structured method ensures that the testing process is systematic, measurable, and well-documented. A total of 23 test cases were created and organized into seven test suites covering all major features of the Mandala Chain website. The results show that all test cases passed successfully, indicating that the tested features function as specified. The implementation of automated testing using Katalon Studio effectively improves efficiency, ensures result consistency, and minimizes human error risks in verifying the functionality of blockchain-based systems such as Mandala Chain.